2011
DOI: 10.4028/www.scientific.net/amm.99-100.773
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Cementitious Property of Pumice

Abstract: Because of its poor pozzolan property in tests, the pumice was unsuitable to be used as the cement admixture, which could reduce the compressive strength greatly. In the experiment, the cement,replaced with several ratios of pumice,was stimulated by the different content of mixed solution with sodium silicate and KF. The compressive strength results and the SEM morphologies showed that mixed solutions can display excellent alkali-activated effects on pumice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Additionally, using more, or coarser, pumicite in concrete mixtures may also lead to reduced heat of hydration and compressive strength along with increased setting time and water demand as well as improved ASR resistance and sulfate resistance [46,47]. Another study [48] found that the use of pumicite alone (without catalysts such as sodium silicate and potassium fluoride) showed limited pozzolanic activity.…”
Section: Natural Pozzolanmentioning
confidence: 99%
“…Additionally, using more, or coarser, pumicite in concrete mixtures may also lead to reduced heat of hydration and compressive strength along with increased setting time and water demand as well as improved ASR resistance and sulfate resistance [46,47]. Another study [48] found that the use of pumicite alone (without catalysts such as sodium silicate and potassium fluoride) showed limited pozzolanic activity.…”
Section: Natural Pozzolanmentioning
confidence: 99%
“…A research study by Kabay et al [6] investigated the effect of the partial replacement of pumice and fly ash with cement on the mechanical-physical and durability properties of concrete in Turkey. Liu et al's research [7] investigated pumice-replaced cement's compressive strength and SEM morphologies. Planetary and ball mills are used for grinding the pumice, where smaller particle size increases the specific surface area.…”
Section: Introductionmentioning
confidence: 99%